PID tuning control strategy using Cuckoo Search algorithm - Singh, K.S.M.J. (Institute of Electrical and Electronics Engineers Inc., 2015)
Direct-Current (DC) servo motor precision and accuracy is crucial. Therefore, proper tuning of these motors is crucial. This paper focuses on using nature-inspired metaheuristic algorithms due to its' capability to improve the current control systems in terms of rise time, settling time, overshoot and steady state error. Algorithms that have been investigated are the Cuckoo Search (CS) in tuning the Proportional-Integral-Derivative (PID) controller. Â© 2015 IEEE.